North Africa's menace : AQIM's evolution and the U.S. policy response - Chivvis, Christopher S.; Liepman, Andrew; International Security and Defense Policy Center; National Defense Research Institute (U.S.); Rand Corporation; United States. Department of Defense. Office of the Secretary of Defense (Santa Monica, CA : RAND, 2013)
Since the 9/11 attacks, America$1 (Bs understanding of Al Qaeda has evolved along with the organization itself. In recent years attention to Al Qaeda$1 (Bs so called (3z(Baffiliates(3y (Bin Iraq, Yemen, Somalia, and most recently Syria has overtaken concern about Al Qaeda$1 (Bs core in Pakistan. The North African terrorist organization Al Qaeda in the Islamic Maghreb (AQIM) is one such affiliate. Many Americans first became familiar with AQIM when media reports linked it loosely to the attacks on the U.S. diplomatic compounds in Benghazi, Libya on 9/11/12 that killed U.S. Ambassador to Libya Chris Stevens. The horrific hostage crisis at an Algerian gas facility in January 2013, which was far more closely linked to the group, further increased concern about the threat it posed and played into anxieties about what many viewed as a resurgent Al Qaeda threat. This assessment of the threat from AQIM is based on an analysis of available open-source documentation. The authors find that although AQIM is a serious regional problem, its similarity to the Al Qaeda of Osama Bin Laden should not be exaggerated, as AQIM does not currently seem bent on global jihad. In most situations, the wisest policy responses to the AQIM threat will focus on supporting local actors and U.S. allies in Europe.s
"RAND Corporation."
"This research was conducted within the International Security and Defense Policy Center of the RAND National Defense Research Institute"--Back cover.
Caption title.
Includes bibliographical references (p. 17-19).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Qaeda in the Islamic Maghreb; Terrorism -- North, Africa